THE INFLUENCE OF SLACK LIME TO CLAY TOWARDS OPTIMUM MOISTURE CONTENT (OMC) AND MAXIMUM DRY DENSITY (MDD) - Bambang Eko Widyanto; Yanyan Agustian; Asep Setiawan (Universitas Widyatama, 2019)
An increase of popilation in Indonisa, especially in West Java make big changes in land use. Green area had been changed to housing, lime hills were mined and it makes several disaster like flood was happened in a high land and landslide happened in a steep area. A reason of landslide happened is the burden of weight soil is higher than it